2015
DOI: 10.3945/jn.114.206565
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Iron-Folic Acid Supplementation Reduces Neonatal and Under-5 Mortality in Nepal

Abstract: Antenatal IFA supplementation significantly reduces the risk of neonatal and under-5 deaths in Nepal. The greatest effect on child survival was found in women who started IFA early in pregnancy and took 150-240 supplements. Universal IFA coverage could improve neonatal and child survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Distribution of IFA and referral to ANC are performed at the community level by Female Community Health Volunteers in Nepal as part of an integrated delivery platform, where adherence and coverage rates are among the highest (Pokharel et al, ). Recent evidence from Nepal shows an association between IFA and newborn or child survival, with the greatest effect in women who started taking IFA early in pregnancy and took 150–240 supplements (Nisar et al, ). Yet regardless of the distribution point, supply‐side issues of adequate supplies of quality IFA tablets and distributing them in adequate amounts to women must also be addressed (Ayoya, Bendech, Zagre, & Tchibindat, ; Galloway et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution of IFA and referral to ANC are performed at the community level by Female Community Health Volunteers in Nepal as part of an integrated delivery platform, where adherence and coverage rates are among the highest (Pokharel et al, ). Recent evidence from Nepal shows an association between IFA and newborn or child survival, with the greatest effect in women who started taking IFA early in pregnancy and took 150–240 supplements (Nisar et al, ). Yet regardless of the distribution point, supply‐side issues of adequate supplies of quality IFA tablets and distributing them in adequate amounts to women must also be addressed (Ayoya, Bendech, Zagre, & Tchibindat, ; Galloway et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Universal iron and folic acid (IFA) supplementation for anaemia prevention among pregnant women is one of the top‐ranked interventions recommended to improve maternal survival (Campbell, Graham, & Lancet Maternal Survival Series Steering Group, ). Recent evidence suggests that it may also be associated with improved neonatal and child survival (Nisar, Dibley, Mebrahtu, Paudyal, & Devkota, ). In 2012, the World Health Organization (WHO) updated its guidelines for IFA supplementation in pregnant women, continuing to recommend daily oral IFA supplementation (with a dose of 30–60 mg elemental iron and 400 μg folic acid) throughout pregnancy to reduce the risk of low birthweight, maternal anaemia, and iron deficiency (WHO, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been suggested to impact the secretion of B-vitamins in human milk, such as nutritional status of the mothers during pregnancy [31], supplementation [8,[16][17][18][19][20], diurnal variation [32], and preterm status of the infants [33]. In addition, maternal age [34], body weight index (BMI), education, income, and regular exercise [35] may also modify B-vitamins status in human milk.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches [5,6,8,[11][12][13][14][15] showed that the contents of B-vitamins in human milk were significantly affected by maternal status and dietary intake. Moreover, maternal deficiency can rapidly result in very low concentrations of B-vitamins in human milk [5], which has been shown to improve with dietary supplements [8,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal diet during pregnancy has been shown to impact fetal growth and development (Liu et al, 2015; Nisar, Dibley, Mebrahtu, Paudyal, & Devkota, 2015; Shapiro et al, 2016). Maternal high-fat diet (HFD) in particular has been shown to be causally associated with higher offspring adiposity and size at birth in animal models (Ashino et al, 2012; Franco et al, 2012; S.…”
Section: Introductionmentioning
confidence: 99%